(untitled) (Biological Sciences - PJSIR, 2022)
Two greenhouse studies were undertaken in 1988 and 1989 at University of Wyoming, Laramie, USA to determine the effects of N alone N + P placement methods on downy brome infested wheat grown in pots with normal irrigation and waterstress. Results of the first ex peri ment showed that blend of Nand P gave 20% more downy brome tillers than an application of N only. Similarly, surface broadcasting of NP fertilizer produced greater tiller numbers (44%) and dry matter yield (28%) of downy brorne compared to the deep placement of the same nutrients. Deep banded NP fertilizer showed promise for greater plant height (13.6 em), ear length (2.9cm), grain yield (24%) and straw yield (26%) of wheat in comparison with surface broadcast application treatment. In second greenhouse study (J 989), water stressed and unstressed treatments differed significantly from each other in downy brome dry matter yield, wheat yield components and wheat dry matter production. Deep banding treatment, compared with broadcasting ofNP, afforded relatively lower downy brome dry matter yield and higher grain and dry matter yield of wheat.